IMPLIKASI PUISI “AKU MANUSIA” KARYA KH. MUTHOFA BISRI TERHADAP PENDIDIKAN ISLAM - Anam, Saeful; Masyhudi, Habib (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
This research article aims to describe the poem "Aku Manusia" by KH. Musthofa Bisri and its implications for Islamic education. The research method used is literature research by reviewing several literature and analyzing substantively with experts. The results of this study show that the poetry collection book entitled "I am Human" has Islamic educational values that can be applied in everyday life, namely the value of piety, social values, and moral education values. This book of poetry collection I am Human shows that literary works can also be used as a medium for da'wah and learning media.